Hierarchical FAU‐ and LTA‐Type Zeolites by Post‐Synthetic Design: A New Generation of Highly Efficient Base Catalysts. (7th November 2012) - Verboekend, Danny; Keller, Tobias C.; Mitchell, Sharon; Pérez‐Ramírez, Javier
Abstract Hierarchical FAU‐ and LTA‐type catalysts are prepared by post‐synthetic modifications and evaluated in the base‐catalyzed Knoevenagel condensation of benzaldehyde with malononitrile. A novel route to attain mesoporous Al‐rich zeolites (A and X) is demonstrated, while mesoporous Y and USY zeolites are prepared using recently developed methods. Base functionality is introduced by alkali ion exchange (Cs, Na) or by high‐temperature nitridation in ammonia. A thorough characterization of the zeolites' structure, composition, porosity, morphology, and basicity demonstrates that the presence of a secondary mesopore network enhances the ion‐exchange efficiency and the structural incorporation of nitrogen. The modified USY zeolites display twice the conversion, while the hierarchical A, X, and Y are up to 10 times more active based on the enhanced accessibility. These results demonstrate that the Knoevenagel condensation takes place predominately at the external surface, highlighting secondary porosity as a key criterion in the design of basic zeolite catalysts.